Representation of citizenship and the confidence in the democracy according to the educative level in young people of 18 to 23 years in Lima Metropolitan - Arenas Iparraguirre, Carlos (2004)
Objective: To know the representation the citizenship and the confidence of the democracy according to the educative level in young people of 1823 years of Lima Metropolitan. DESIGN: Comparative cross-sectional. The population was confirmed by young people between 18 to 24 years students of the last secondary level of trainings and last academic cycles of two national universities, with a no probabilistic sampling of intentional type. MATERIAL And METHODS: The used instruments were the technique of the Focus Groups for the representation of the citizenship and the Scale Rating for the confidence in the democratic institutions. RESULTS: The analysis of the results was by means of percentage calculations with respect to the indicators of the citizen representation: finding difference between the students of secondary and the college students, in the first DNI it is the representation of citizenship, in the college students it is framed within the Rights and Duties; nevertheless, near a 1% they do not present display a level of abstraction different from those from the secondary level. As far as the confidence in the democracy it is appraised that there is no significant difference between both groups of students. CONCLUSIONS: One concluded that the level of confidence in the democracy of the scholastic young people and of university students is low, expressed in identifying to the present government with the democratic system, the representation of citizenship 01 the scholastic young people is different from the university students, due to soon the entrance to the labor field and the personal commitment that they have, having the educative level a direct influence on the confidence in the democracy: the university student has a greater preoccupation by the problems of the country and by the paper that corresponds to him to each individual in the sphere of the public decisions that the young student who do not problematical the exercise of their rights and very few express slight knowledge related to the confidence in the democracy.